Unveiling the grip of mobile phone addiction: an in-depth review - Li, Jinyu; Yang, Hong (Frontiers in Psychiatry, 2024)
Mobile Phone Addiction represents an emergent addictive disorder that gravely jeopardizes the physical and mental health of adolescents worldwide, necessitating exhaustive research. Current reviews of MPA are in dire need of updates and enhancements. Therefore, this review aggregates the extant research spanning the past two decades on the prevalence, pathogenesis, comorbidities, assessment, and treatment of MPA, aiming to furnish a reference for future investigations into this condition.